Penal Policy Cybercrime Artificial Intelligence (AI) Era Society 5.0 Presfektif Fiqih Jinayah dan Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik - Iriani, Dewi (Institut Agama Islam Negeri Ponorogo, 2024)
Cybercrime is increasing in line with the advancements of the era, triggering the need for legal protection governing the use of Artificial Intelligence (AI). This research aims to develop a penal policy that provides protection for victims of AI-based cybercrime by addressing two main issues: 1) the concept of prohibiting AI-based cybercrime in the Society 5.0 era from the perspective of Fiqh Jinayah and 2) the urgency of penal policies in protecting victims of AI-based cybercrime in this era. Using a qualitative normative approach, the study analyzes legal frameworks, including Law Number 19 of 2016 on Electronic Information and Transactions, and integrates the theories of Penal Policy and Fiqh Jinayah as analytical foundations. The findings reveal that, from the Fiqh Jinayah perspective, AI-based cybercrime is categorized as jarimah, subjecting perpetrators to hudud punishments under Law Number 1 of 2024. Furthermore, the urgency of penal policies lies in strengthening government regulations, requiring official registration of all internet applications through the Ministry of Communication and Information (Kemeninfo). Recommendations include fostering inter-agency collaboration, involving IT experts in mapping hacking threats, and focusing on enhanced cybersecurity measures